Erythropoiesis and performance after two weeks of living high and training low in well trained triathletes - Dehnert, C.; Hutler, M.; Liu, Y.; Menold, E.; Netzer, C.; Schick, R.; Kubanek, B.; Lehmann, M.; Boning, D.; Steinacker, J. M. (International Journal of Sports Medicine, 2002)
The purpose of our study was to evaluate hematologic acclimatization during 2 weeks of intensive normoxic training with regeneration at moderate altitude (living high-training low, LHTL) and its effects on sea-level performance in well trained athletes compared to another group of equally trained athletes under control conditions (living low - training low, CONTROL). Twenty-one triathletes were ascribed either to LHTL (n = 11; age: 23.0 +/- 4.3 yrs; Vdot;O 2 max: 62.5 +/- 9.7 [ml x min -1 x kg -1]) living at 1956 m of altitude or to CONTROL (n = 10; age: 18.7 +/- 5.6 yrs; Vdot;O 2 max: 60.5 +/- 6.7 ml x min -1 x kg -1) living at 800 m. Both groups perfomed an equal training schedule at 800 m. Vdot;O 2 max, endurance performance, erythropoietin in serum, hemoglobin mass (Hb tot, CO-rebreathing method) and hematological quantities were measured. A tendency to improved performance in LHTL after the camp was not significant (p < 0.07). Erythropoietin concentration increased temporarily in LHTL (Delta 14.3 +/- 8.7 mU x ml -1; p < 0.012). Hb tot remained unchanged in LHTL whereas was slightly decreased from 12.5 +/- 1.3 to 11.9 +/- 1.3g x kg -1 in CONTROL (p < 0.01). As the reticulocyte number tended to higher values in LHTL than in CONTROL, it seems that a moderate stimulation of erythropoiesis during regeneration at altitude served as a compensation for an exercise-induced destruction of red cells.